METHOD AND SYSTEM FOR GENERATING INDEXED CORPUS FOR DOMAIN-DRIVEN KNOWLEDGE AUGMENTED QUESTION ANSWERING - RATH, PURNENDU KUMAR; DAS, PRASENJIT; BASAVARSU, PURUSHOTTHAM GAUTHAM (2025)
Existing question answering approaches have the disadvantages that they possess limited contextual understanding due to which the retrieval process they use is inefficient in nature. Embodiments disclosed herein provide a method and system for domain-driven knowledge augmented question answering. The system receives a raw corpus data as input, wherein the raw corpus data is a domain specific data. Further, an indexed corpus is generated from the raw corpus data, during which a document chunking approach is used. The indexed corpus is then used for processing received queries received, in order to generate response to the received user queries.